2012
DOI: 10.1016/j.jmoldx.2011.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Components Affect Accuracy of Circulating Cancer-Related MicroRNA Quantitation

Abstract: Circulating microRNAs (miRNAs) have emerged as candidate biomarkers of various diseases and conditions including malignancy and pregnancy. This approach requires sensitive and accurate quantitation of miRNA concentrations in body fluids. Herein we report that enzyme-based miRNA quantitation, which is currently the mainstream approach for identifying differences in miRNA abundance among samples, is skewed by endogenous serum factors that co-purify with miRNAs and anticoagulant agents used during collection. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
156
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(163 citation statements)
references
References 56 publications
2
156
1
4
Order By: Relevance
“…Also, the different kind of anticoagulants used can influence the results. Thus, Kim et al [26] observed that the levels of miR-16 and miR-223 are lower when heparin is used and higher with oxalate, while EDTA provides similar results to serum. Hemolysis is also a factor that affects the analysis of some miRNAs, including miR-16, miR-451, miR-92a and miR-486-5p that are released by erythrocytes [27,28].…”
Section: Preanalytical and Analytical Variables In Mirna Measurementmentioning
confidence: 99%
“…Also, the different kind of anticoagulants used can influence the results. Thus, Kim et al [26] observed that the levels of miR-16 and miR-223 are lower when heparin is used and higher with oxalate, while EDTA provides similar results to serum. Hemolysis is also a factor that affects the analysis of some miRNAs, including miR-16, miR-451, miR-92a and miR-486-5p that are released by erythrocytes [27,28].…”
Section: Preanalytical and Analytical Variables In Mirna Measurementmentioning
confidence: 99%
“…For additional profiling of unfractionated plasma or serum, the foremost concerns are to establish standardized sampling and processing protocols (43)(44)(45)(46); account for the effects of RNA extraction methods (9,47,48 ), profiling platforms (49,50 ), and analysis (46 ); and develop and adhere to norms for reporting of methods and data (12,(51)(52)(53)(54). These issues have been addressed adequately elsewhere and also apply to other biofluids and more-focused studies on EVs.…”
Section: Profiling Of Unfractionated Plasma or Serummentioning
confidence: 99%
“…Heparin is commonly used as an anticoagulant in cardiovascular diagnostics and interventions. Previous studies have demonstrated that heparin can inhibit RNA quantification in vitro by interfering with the DNA polymerase used in the quantitative PCR (qPCR) reaction (3 ). It is unclear, however, whether the biologically active concentrations of heparin achieved after treatment of patients influences the quantification of miRNAs in blood samples.…”
Section: To the Editormentioning
confidence: 99%